ADVANCE CARE PLANNING AMONG AMERICAN INDIANS. (11th November 2018) - Kwak, J; Cho, Y; Lee, Y; Noh, H; Roh, S
Abstract: American Indians (AI) are one of the least studied populations regarding advance care planning 3 (ACP). The available literature suggests aversion to ACP in this group. However, the available literature is based on mostly qualitative and descriptive studies, and lacks systematic investigation of ACP practice among AIs. The goal of this study was to examine the associations between individual factors including race, other sociodemographic, spiritual/religious, and health characteristics, and ACP among AIs and non-AI older adults. A cross-sectional, self-administered in-person survey was conducted with a convenience sample of 200 AI and 436 non-Hispanic White older adults from two Midwestern states. Univariate analysis showed that compared with White peers, AI older adults were significantly less likely to have an end-of-life (EOL) care plan or to have completed a durable power of attorney for health care (DPOHC) or a living will. Multivariate analysis showed that having an EOL plan was associated with older age, some college education or more, and a greater number of chronic conditions, but not with race; whereas having a DPOHC and living will was associated with being White. Lower rates of formal ACP among AIs suggest implications for targeted culturally sensitive approaches to promoting ACP, grounded in and understanding of indigenous cultures' health beliefs and practices, as well as high standards for quality palliative care.